A Comparative Study of the Social Sector at Global Level (With Special Reference to Public Health of India) Dr. Anjali Jain1* Runa Paul2: A Comparative Analysis of Public Health Systems in India and Other Countries (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Social sector is an important sector for any economy and includes several important component such as education, health and medical care, water supply and sanitation, poverty alleviation, housing conditions etc. that play a vital contribution in human development. The elements of liberalization and economic reforms have played a key role in the areas of social infrastructure and development but on the other aspect it has also led to the commercialization of the health sector leading to high out of pocket expenditure (OOP). Important aspects of human development are now governed within economic sphere where market and private philanthropy play a vital role. Due to the rapidly globalizing competitive marketplace coupled with the increasing need to expand quality of life at the grassroots level and to spur innovative thought, policy makers in India are slowly but surely setting the social sector on the reform track. Our paper focuses on the condition of the public health system of India. The paper has been divided into three sections, the I section is based on introduction about social sector along with the objectives and methodology of the study. In the II section an attempt is made for a comparative analysis in regarding various aspects of the social sector of India & other countries of the world. Section III briefly summarizes the conclusion of the study.